2019
DOI: 10.21680/1982-1662.2019v2n25id17308
|View full text |Cite
|
Sign up to set email alerts
|

Entre O Fogão E a Ciência

Abstract: Atualmente, compreende-se que a comida e alimentação tem se expandido enquanto ciência, sendo objeto de estudo científico e sensorial na atualidade, quando estudos sociológicos, antropológicos e também nutricionais se deleitam não somente sobre as problemáticas de saúde do indivíduo, mas também a saúde coletiva e desenvolvimento social, formação e transformação cultural, memória ancestral e construção de tradições por meio da comensalidade. Esse fato implica na compreensão de que a comida se diferencia do alim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It is essential the power of tradition ahead of the preparation of "caiçaras recipes" and that Campesinos protect the important bicultural patrimony, with knowledge of practices of agroecological basis and gastronomic culture. However, we observed that few were the works found, indicating a shortfall of research in these areas, besides showing the necessity of bigger studies, registers and valorisation of traditional eating habits, as well as its social relevance both in terms of feeding sovereignty and the preservation of the environment.food and the act of cooking and eating (Barbosa, 2019;Canesqui, 2005). According to the dictionary New Concise Larousse Gastronomique the term gastronomy is recent: "the entry gastronomy comes from ancient Greek, gastros stomach + nomiaknowledge/law" (Hamlyn, 2011, p. 545, our translation).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…It is essential the power of tradition ahead of the preparation of "caiçaras recipes" and that Campesinos protect the important bicultural patrimony, with knowledge of practices of agroecological basis and gastronomic culture. However, we observed that few were the works found, indicating a shortfall of research in these areas, besides showing the necessity of bigger studies, registers and valorisation of traditional eating habits, as well as its social relevance both in terms of feeding sovereignty and the preservation of the environment.food and the act of cooking and eating (Barbosa, 2019;Canesqui, 2005). According to the dictionary New Concise Larousse Gastronomique the term gastronomy is recent: "the entry gastronomy comes from ancient Greek, gastros stomach + nomiaknowledge/law" (Hamlyn, 2011, p. 545, our translation).…”
mentioning
confidence: 92%
“…food and the act of cooking and eating (Barbosa, 2019;Canesqui, 2005). According to the dictionary New Concise Larousse Gastronomique the term gastronomy is recent: "the entry gastronomy comes from ancient Greek, gastros stomach + nomiaknowledge/law" (Hamlyn, 2011, p. 545, our translation).…”
mentioning
confidence: 99%